2013
DOI: 10.1074/jbc.m113.485128
|View full text |Cite
|
Sign up to set email alerts
|

The Catalytic Domain of Topological Knot tRNA Methyltransferase (TrmH) Discriminates between Substrate tRNA and Nonsubstrate tRNA via an Induced-fit Process

Abstract: Background: Topologically knotted tRNA methyltransferases specifically recognize substrate tRNA. Results: Site-directed mutagenesis studies, chimeric protein analysis, and pre-steady state kinetics clarify the tRNA recognition sites of TrmH. Conclusion:The N-and C-terminal regions function in the initial binding process, and substrate tRNA is discriminated by the catalytic domain in an induced-fit process. Significance: Study of how proteins recognize RNA is crucial for understanding RNA maturation processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 66 publications
1
49
0
Order By: Relevance
“…While the TrmD-fold is the least common among the five folds, the Trm5-fold is present in the greatest majority of AdoMet methyl transferases. Intriguingly, the TrmD-fold is present in TrmH, which catalyzes methyl transfer to G18 to give G m 18 (G m = 2′-O-methyl of G) at the tRNA tertiary core (Ochi, et al, 2013). Although Mg 2+ was reported to increase activity of TrmH, spermine had a similar effect (Kumagai, et al, 1982), thus leaving open the question of how the metal ion facilitated this methyl transfer.…”
Section: Resultsmentioning
confidence: 99%
“…While the TrmD-fold is the least common among the five folds, the Trm5-fold is present in the greatest majority of AdoMet methyl transferases. Intriguingly, the TrmD-fold is present in TrmH, which catalyzes methyl transfer to G18 to give G m 18 (G m = 2′-O-methyl of G) at the tRNA tertiary core (Ochi, et al, 2013). Although Mg 2+ was reported to increase activity of TrmH, spermine had a similar effect (Kumagai, et al, 1982), thus leaving open the question of how the metal ion facilitated this methyl transfer.…”
Section: Resultsmentioning
confidence: 99%
“…TrmHs can be divided into 2 subclasses; one can recognize all tRNA species, whereas the other, including EcTrmH, can only modify a subset of tRNA species. 27 Early study suggested that G18G19 and the D-arm structure of the tRNA are essential requirements for recognition by Thermus thermophilus TrmH, 21 but further work showed that T. thermophilus TrmH recognized G18 with some flexibility and the oxygen 6 of G18 was the crucial determinant for TrmH recognition. 25 TrmD is a tRNA (m 1 G37) MTase.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23][24] Substitution at G18G19 causes deficiencies in methyl transfer activity, and the oxygen 6 atom of G18 is a key recognition element for TrmH. [25][26][27] TrmD and TrmJ act on the tRNA anticodon loop. TrmD is a tRNA (m 1 G37) MTase, [28][29][30][31][32] containing an extension sequence for tRNA binding, in contrast to TrmL.…”
Section: Introductionmentioning
confidence: 99%
“…To confirm this, we performed a gel mobility shift analysis. As reported by Droogmans et al (20), it is much more difficult to perform gel mobility shift assays with TrmI than with other tRNA modification enzymes (53,54) because the large TrmI tetramer (more than 100 kDa) does not migrate into a normal polyacrylamide gel under electrophoresis. Consequently, we used agarose gels for the gel mobility shift assay as reported (20) and stained them with ethidium bromide.…”
Section: Replacement Of A58 By I Causes the Complete Loss Of Methyl Gmentioning
confidence: 98%